2020
DOI: 10.1002/fsn3.2080
|View full text |Cite
|
Sign up to set email alerts
|

Effects of orange peel powder on rheological properties of wheat dough and bread aging

Abstract: Orange peels, the major byproduct of orange fruit processing, are a good material for functional food production because of their excellent physiological and health function. The effects of orange peel powder (OPP) on the rheological and reho‐fermentation properties of high‐gluten wheat dough and bread staling were investigated. The results showed that OPP significantly modified wheat dough characteristics and bread quality for its fiber, pectin and polyphenol content. Incorporation of OPP in wheat dough mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 36 publications
(40 reference statements)
3
22
0
1
Order By: Relevance
“…The rheograms showed that the elastic modulus values were higher than viscous modulus values (G′ > G″), representing the elastic behavior of dough samples. Similar elastic behavior was reported in dough enriched with orange peel powder (Han et al, 2021).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The rheograms showed that the elastic modulus values were higher than viscous modulus values (G′ > G″), representing the elastic behavior of dough samples. Similar elastic behavior was reported in dough enriched with orange peel powder (Han et al, 2021).…”
Section: Resultssupporting
confidence: 84%
“…The Dynamic Rheological characteristics of dough were determined in terms of storage (G′) and loss moduli (Gʺ) as a function of frequency (0 to 100 cm) with constant stress (1.0 Pa) at 30°C temperature using a Rheometer (MCR102, M/s. Anton Paar, Austria) by following the method adapted from Han et al (2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrophilic characteristics of gluten in flour can be enhanced during bread making by the addition of pectins and polyphenols as well by the formation of H bonds with water, polyphenols and polysaccharides [ 33 ]. Moreover, Han et al demonstrated that when the addition of orange peel powder was no greater than 5%, a significant inhibition in the retrogradation of wheat dough was detected, while an opposite tendency was observed with higher percentages [ 94 ]. However, changes in the mechanism of staling, as well as structure modification as a consequence of fortification, should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Increased viscosity of the dough is due to the presence of an extract containing high amounts of flavonoids, tannins with high water absorption capacity [3,[16][17][18].…”
Section: Resultsmentioning
confidence: 99%